Liquid culture for isolating microorganisms with potential to degrade methyl parathion from agricultural soils and organic waste (2012)
ABSTRACT: The search for microorganisms with high capacity for pesticide degradation is a very interesting attempt to approach bioremediation strategies in order to prevent contamination. This study evaluates the potential of agricultural soils and solid orga-nic waste cultures microbial isolation as a strategy for screening microorganisms with potential for Methyl parathion (MP) degradation. For the study, microbial consortia were recovered from the liquid fraction of suspension cultures of agricultural soils and solid organic waste. Then, the MP degradation ability and its toxic effect on microbial activity were determined during microbial incubations under laboratory controlled conditions. The results showed that it is not possible to recover the active microorganisms that have potential to degrade the MP from the agricultural soils. However, an active consortium that would degrade both MP and its degradation products was isolated from the organic solid waste